Use of diet and body condition assessments as intermediate indicators of translocation success in the Critically Endangered Philippine crocodile (Crocodylus mindorensis). Issue 10 (9th September 2021) - Brown, Joseph C.; Shirley, Matthew H.; Yog‐yog, Amante; van Weerd, Merlijn; Balbas, Marites G.; Tarun, Bernard A.; Siler, Cameron D.
Abstract: Intermediate metrics of translocation success are useful for long‐lived, slow to mature species where survival and reproduction happen over decades. With fewer than 150 individuals in the wild, the Critically Endangered Philippine crocodile ( Crocodylus mindorensis ) is one of the most threatened species on Earth. This study presents the first analysis of diet and body condition of wild Philippine crocodiles and headstarted (i.e. captive‐reared) individuals released into the wild over the last decade, and uses these results to show how diet and body condition can be pertinent intermediate metrics of translocation success. Analyses of stomach contents revealed 17 different aquatic and terrestrial invertebrate and vertebrate prey species. Interestingly, 70% of Philippine crocodiles showed snails to be the predominent prey type, followed by fish (36.7%), birds (33.3%) and reptiles (33.3%). More than 50% of crocodiles consumed the invasive golden apple snail, a leading agricultural pest. Regardless of crocodile history (wild vs. headstarted) or size class (juvenile vs. adult), no evidence was found for dietary differences in percentage occurrence, percentage composition or prey diversity. Body condition was significantly higher in wild compared with headstarted individuals when analysed together in a pooled group, although neither group differed significantly from the standardized expectation, and headstarted individuals were not significantly different when body condition was derived independently for the two groups. This study provides a working example of how assessing the convergence of diet and body condition between translocated and wild individuals can provide complementary monitoring parameters to demonstrate post‐release establishment of translocated crocodylians. The congruent dietary composition and comparable body condition observed in this study suggest that headstarted crocodiles adapt well following release. Crocodylus mindorensis survives in an agricultural landscape and is likely to play an ecologically important role by exploiting invasive species, reinforcing the importance of this species to local communities.